WASP (Write a Scientific Paper): Structuring a scientific paper. (January 2019) - Cuschieri, Sarah; Grech, Victor; Savona-Ventura, Charles
Abstract: Writing and publishing scientific papers have become requisites for all scientists (researchers and academics alike) to maintain their professional career. The prospects of writing a scientific paper are often regarded as somewhat daunting to the uninitiated. However a universal, well established structure format known as "IMRAD": i.e. Introduction, Methods, Results And Discussion has been established. This paper details this methodology.